Complexity and values in nurse education : dialogues on professional education - Martin, Lipscomb (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Providing a critical discussion of issues faced by educators when ideas from outside of nursing conflict with normatively inspired outcomes that students are required to accept, this book explores the interplay of complexity and values in nurse education from a variety of vantages. Thought-provoking, challenging, and occasionally rumbustious in tone, this volume has something to say to both nurse educators (who may find cherished practices questioned) and students. Moreover, given the breadth and nature of subjects covered the book will also appeal to anyone concerned about and interested in nursing's professional development/trajectory"--
Keywords: Nursing -- Study and teaching; MEDICAL / Nursing / Research & Theory; EDUCATION / Professional Development; EDUCATION / Philosophy & Social Aspects